Potential applicaton of β-galactosidase in food science and nutrition - Nika ŽIBRAT; Mihaela SKRT; Polona JAMNIK (Acta Agriculturae Slovenica)
β-galactosidase is an enzyme with hydrolytic and transgalactosylation activity. The origin of the enzyme dictates the balance between both activities. Industrially used β-galactosidases are obtained with recombinant production from filamentus funghi Aspergillus sp. and yeasts Kluyveromyces sp. Recently thermostabile β-galactosidases have been subject of many research. The enzyme can be industrially used in free or immobilized form. Immobilization often provides better stability, reusability and lower expenses. Application of β-galactosidase is most common in food processing and nutrition, it is also used in medicine and ecology. Hydrolytic activity of the enzyme has long been used for reducing lactose content in milk, while transgalactosylitic activity is used for synthesis of products such as galactooligosaccharides, lactosucrose and others. The latter have a great potential in food industry for obtaining products with reduced lactose content and increasing of nutritional value by adding dietetic fibers such as galactooligosaccharides. Despite the potential it is vital that reaction mechanisms become better understood and optimization is in place in order to reach the usability of this enzyme at industrial level.